Special Education Teachers’ Perceptions Toward Online Learning During the Covid-19 Pandemic - Vania Martha Yunita; Sunardi Sunardi; Agus Kristiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Distance learning or online learning is one of the impacts caused by the Covid-19 Pandemic. Many problems occur during online learning, including special education teachers. The purpose of this study was to see the perceptions of special education teachers towards distance learning or online learning carried out for children with special needs. This research uses descriptive analysis with case study method. The data were collected using questionnaire questions and the data were analyzed using inductive and thematic analytics. The results of the survey conducted showed that there are still many teachers with special needs who have difficulty with distance learning for children with special needs so that there is a need for the development of creativity from teachers in learning during the pandemic.